(untitled) (Journal of Human Sciences, 2025)
The purpose of the study is to determine the speaking challenges that University of Ajdabiya English language learners encounter and the reasons behind these challenges. To gauge the speaking challenges faced by English language learners in the second, third, and fourth semesters, the researcher employed a questionnaire divided into two linguistic and psychological categories and given to 67 students. The study aimed to determine the challenges that University of Ajdabiya students faced during their second, third, and fourth semesters. It also covered the hunt for potential fixes and suggestions to deal with these issues. The findings indicated that students had some difficulty communicating for a variety of reasons, and psychological factors including shyness, worry, lack of confidence, and fear of making mistakes were the primary cause.